Penerapan evidence-based nursing practice (EBNP) mengenai intervensi virtual reality (VR) dalam mengurangi kecemasan pada pasien yang menjalani coronary angiography - Hendi, Oman; Jumaiyah, Wati; Latipah, Siti; Rayasari, Fitrian; Anggraini, Dewi (Holistik Jurnal Kesehatan, 2025)
Background: Coronary angiography is used as an appropriate method for diagnosing coronary artery disease (CAD), which is the radiographic visualization of coronary arteries after the injection of radiopaque contrast media. However, patients undergoing coronary angiography experience anxiety. With advancements in technology, various innovations have emerged offering non-invasive alternatives for managing anxiety in patients undergoing coronary angiography. One innovative approach currently under development is the use of Virtual Reality (VR). Purpose: To determine the effect of VR in reducing anxiety in patients undergoing coronary angiography.  Method: This EBNP application is experimental, using a pre-post test design with a sample size of 30 patients. VR intervention was administered to patients undergoing coronary angiography for 30 minutes. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI) questionnaire. Results: The VR intervention showed a reduction in anxiety, with a p-value of 0.000, which is less than the alpha level of 0.05, indicating a significant difference in anxiety levels before and after the VR intervention in patients undergoing coronary angiography.  Conclusion: The VR intervention has a positive effect in reducing anxiety in patients before coronary angiography.   Keywords: Anxiety; Coronary Angiography; Coronary Artery Disease; Virtual Reality.   Pendahuluan: Coronary angiography digunakan sebagai metode yang tepat untuk mendiagnosis penyakit jantung koroner yang merupakan  visualisasi radiografi pembuluh darah koroner setelah penyuntikan media kontras radiopak. Akan tetapi, pasien yang menjalani coronary angiography mengalami kecemasan.  Seiring dengan perkembangan teknologi terdapat berbagai inovasi yang menawarkan alternatif noninvasif dalam pengelolaan kecemasan pada pasien yang menjalani coronary angiography. Salah satu pendekatan inovatif yang sedang berkembang adalah penggunaan virtual reality (VR). Tujuan: Untuk mengetahui pengaruh penerapan evidence-based nursing practice (EBNP) mengenai intervensi virtual reality (VR) dalam mengurangi kecemasan pada pasien yang menjalani coronary angiography. Metode: Penerapan EBNP ini bersifat eksperimen menggunakan desain pre-post test design dengan jumlah sampel sebanyak 30 partisipan. Intervensi VR pada pasien yang menjalani coronary angiography selama waktu 30 menit. Melakukan pengukuran kecemasan 15 dengan kuesioner state trait anxiety inventory (STAI). Hasil: Intervensi VR menunjukkan menurvensi VR paru) mencapai 6,penurunan kecemasan diperoleh (p Value) 0.000 ≤ 0.05 yang berarti terdapat perbedaan signifikan kecemasan sebelum dan setelah dilakukan intervensi VR pada partisipan yang menjalani coronary angiography. Simpulan: Intervensi VR memberikan pengaruh positif dalam mengurangi kecemasan pasien sebelum tindakan coronary angiography.   Kata Kunci: Coronary Angiography; Coronary Artery Disease; Kecemasan; Virtual Reality.